Endocrine pancreas development at weaning in goat kids - Fabia Rosi; Luca Cerri; Silvia Modina; Ahmed Atef Aufy; Damiano Magistrelli (Italian Journal of Animal Science, 2010)
Eighteen three-day old Saanen goat kids were divided into MILK and WEAN groups. MILK kids received goat milk to age 48 days; WEAN kids were initially fed milk but started weaning at 25 days and were completely weaned by 40 days. Total intake per group was recorded daily. On day 25, 40 and 48, body weights were recorded, and plasma samples were taken and analyzed for glucose, free amino-acids and insulin. On day 48, all animals were slaughtered and pancreas samples were analyzed for total DNA and RNA content. Histological sections of pancreas were examined by light microscope and images analyzed by dedicated software. Seven days after the beginning of the weaning program, dry matter intake in the WEAN group began to decrease compared to the MILK one. Nonetheless, body weight did not differ throughout the study period. Weaning significantly decreased plasma levels of glucose, amino-acids and insulin. No difference was observed in pancreatic DNA and RNA content. Histological analysis of pancreas showed that the size of pancreatic islets was not different, but islet number per section was lower in the pancreas of WEAN animals. In conclusion, weaning affects glucose and amino-acid metabolism and influences endocrine pancreas activity and morphology.